SLC4A10 impedes atherosclerosis by diminishing IFN-γ/GZMB levels of CD8+ T cells via the MAPK pathway - Chen, Bo; Zhu, Lei; Lin, Xueguang; Kwan, Kristine J. S.; Wang, Jie; Lu, Yijie; Li, Jialong; Deng, Ying; Jiang, Shuai; Tang, Jingdong; Yu, Bo (Frontiers in Immunology, 2025)
Background and aimsCD8+ T cell subpopulations participate in the formation of atherosclerotic plaques through activation or exhaustion. Yet, it is unclear which specific subset it critically involved. The SLC4A10+ CD8+ T cell possess atherogenic attributes and this study aimed to investigate the associated pathway involved in affecting plaque stability.MethodsCarotid plaques were collected from patients that underwent carotid endarterectomy in our institute and categorized into stable or unstable plaques. The SLC4A10+ CD8+ T cell subset were investigated. For in vivo analysis, carotid artery tangem ligation was performed in 8-week-old, AAV-6 overexpressed mice fed with high-fat diet to acquire unstable carotid plaques. Isolated CD8+ T cells were cultivated and their immunopathological characteristics were examined in vitro.ResultsSLC4A10+ CD8+ T cells were significantly enriched in unstable human carotid plaques and were correlated with the apoptosis of vascular smooth muscle cells (VSMCs). SLC4A10-overexpressed mice, serum IL-4, IL-17A, and IL-6 were increased, while the level of granzyme B (GZMB) decreased. The extent of atherosclerotic plaques was mitigated, the amount of collagen fibers were diminished, and the apoptosis of VSMCs were alleviated. Flow cytometry suggested that SLC4A10 decreased the levels of IFN-γ and GZMB in CD8+T cells. The CCK8 demonstrated that IFN-γ and GZMB lead to the decrease in MOVAS cell viability. KEGG analysis revealed that SLC4A10+ CD8+ T cells participated in the MAPK pathway, cytokine-cytokine receptor interaction, TNF signaling pathway, and cell adhesion molecule pathway. The differential expression of related genes MAPK2K6, ELK4, and MAP3K5 in the MAPK pathway were verified.ConclusionsThese data demonstrate that SLC4A10 mitigates cytotoxicity by decreasing the levels of IFN-γ/GZMB of SLC4A10+ CD8+ T cells via the MAPK pathway, which impedes plaque progression and aids stabilization.